Ocular pharmacokinetics of bimatoprost formulated in DuraSite compared to bimatoprost 0.03% ophthalmic solution in pigmented rabbit eyes - Shafiee A (Dove Medical Press, 2013)
Afshin Shafiee,1 Lyle M Bowman,2 Eddie Hou,2 Kamran Hosseini1,3 1Preclinical, 2Development, 3Clinical, InSite Vision, Alameda, CA, USA Purpose: To compare the aqueous humor (AH) and iris-ciliary body (ICB) concentration of bimatoprost in rabbit eyes treated with ISV-215 (0.03% bimatoprost formulated in DuraSite) with the marketed product bimatoprost 0.03% ophthalmic solution. Methods: The left eye of rabbits received a single topical instillation of either ISV-215 (n = 32 eyes) or bimatoprost 0.03% (n = 32 eyes). At predetermined time points, levels of bimatoprost and bimatoprost acid in the AH and the ICB were quantified by HPLC-MS/MS. Results: Both bimatoprost and bimatoprost acid were detected in the AH and the ICB within 15 minutes of dosing. Bimatoprost acid concentrations in both compartments were markedly higher than bimatoprost. There was a statistically significant (P < 0.01) increase in the concentration of the prodrug in the AH and its acid form in the ICB in animals treated with ISV-215 compared to bimatoprost 0.03%. In the ISV-215-treated rabbit eyes, the highest concentrations of bimatoprost and bimatoprost acid were in the ICB and AH, respectively, while in the bimatoprost 0.03%-treated eyes, no differences in the drug content of the selected ocular tissues were observed. Conclusions: Bimatoprost 0.03% formulated in DuraSite has superior ocular distribution and area under the curve compared to bimatoprost 0.03% in rabbit eyes. This improvement in the pharmacokinetic parameters of ISV-215 may provide us with a better platform to optimize a bimatoprost formulation that offers the same degree of efficacy in lowering intraocular pressure and improved therapeutic index in glaucomatous patients by lessening the ocular side effects associated with long-term use of topical prostaglandin F2α analogs. Keywords: drug delivery, intraocular pressure, glaucoma, aqueous humor, prostaglandin (PGF2α) analogs